The Disenchantment of Problems: Musings on a Cognitive Turn in Intellectual History - Asprem, Egil (Journal of religion in Europe, 2015)
This article responds to Hans Kippenberg's, Willem Drees's, and Ann Taves's commentaries on my book, The Problem of Disenchantment. It presents an overview of the key arguments of the book, clarifies its use of Problemgeschichte to reconceptualize Weber's notion of disenchantment, and discusses issues in the history and philosophy of science and religion. Finally, it elaborates on the use of recent cognitive theory in intellectual history. In particular, it argues that work in event cognition can help us reframe Weber's interpretive sociology and deepen the principle of methodological individualism. This helps us get a better view of what the ‘problems’ of Problemgeschichte really are, how they emerge, and why some of them may reach broader significance.